2022
DOI: 10.1038/s12276-022-00811-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced FNDC5/irisin protects nucleus pulposus cells against senescence and apoptosis by activating autophagy

Abstract: Intervertebral disc degeneration (IVDD) is a major cause of low back pain (LBP), and excessive senescence and apoptosis of nucleus pulposus (NP) cells are major pathological changes in IVDD. Physical exercise could effectively delay the process of intervertebral disc degeneration; however, its mechanism is still largely unknown. Irisin is an exercise-induced myokine released upon cleavage of the membrane-bound precursor protein fibronectin type III domain-containing protein 5 (FNDC5), and its levels increase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…IVDD is a chronic process that commonly causes LBP; however, the specific cause of IVDD remains unclear. Published studies have demonstrated that IVDD is a complex process with multifactorial interactions, which is primarily characterized by ECM destruction and cell phenotype changes, as well as apoptosis, autophagy, pyroptosis, necroptosis, and ferroptosis of IVD ( 31 , 104 107 ). The term ferroptosis was first coined in 2012.…”
Section: Ferroptosis and Ivddmentioning
confidence: 99%
“…IVDD is a chronic process that commonly causes LBP; however, the specific cause of IVDD remains unclear. Published studies have demonstrated that IVDD is a complex process with multifactorial interactions, which is primarily characterized by ECM destruction and cell phenotype changes, as well as apoptosis, autophagy, pyroptosis, necroptosis, and ferroptosis of IVD ( 31 , 104 107 ). The term ferroptosis was first coined in 2012.…”
Section: Ferroptosis and Ivddmentioning
confidence: 99%
“…31 Irisin could also protect nucleus pulposus cells against senescence and apoptosis by activating autophagy. 32 And our previous study has also shown that irisin can activate the Akt/eNOS pathway which considered as a survival pathway, and Akt/eNOS pathway may play an important role in the anti-apoptosis effects of irisin.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that irisin could inhibit apoptosis including cardiomyocyte apoptosis, endothelial cell apoptosis and pancreatic β cell apoptosis by the Akt, ERK, p38 MAPK, and TLR/MyD88 signaling pathway 31 . Irisin could also protect nucleus pulposus cells against senescence and apoptosis by activating autophagy 32 . And our previous study has also shown that irisin can activate the Akt/eNOS pathway which considered as a survival pathway, and Akt/eNOS pathway may play an important role in the anti‐apoptosis effects of irisin.…”
Section: Discussionmentioning
confidence: 98%
“…Degenerative discs show reduced brightness and volume. After 8 weeks, the intervertebral discs were scored by the Pfirrmann grading according to the previous research methods [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…After decalcification, dehydration and paraffin embedding were carried out, and then dewaxing, hematoxylin and eosin (H&E) staining, and Safranin-O/fast green staining were carried out. Histological scoring methods refer to previous studies [ 25 ]. ERS-related proteins (caspase-3, GRP78, and CHOP) were detected by immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%